Regulation of Mating-Induced Increase in Female Germline Stem Cells in the Fruit Fly Drosophila melanogaster - Hoshino, Ryo; Niwa, Ryusuke (Frontiers in Physiology, 2021)
In many insect species, mating stimuli can lead to changes in various behavioral and physiological responses, including feeding, mating refusal, egg-laying behavior, energy demand, and organ remodeling, which are collectively known as the post-mating response. Recently, an increase in germline stem cells (GSCs) has been identified as a new post-mating response in both males and females of the fruit fly, Drosophila melanogaster. We have extensively studied mating-induced increase in female GSCs of D. melanogaster at the molecular, cellular, and systemic levels. After mating, the male seminal fluid peptide [e.g. sex peptide (SP)] is transferred to the female uterus. This is followed by binding to the sex peptide receptor (SPR), which evokes post-mating responses, including increase in number of female GSCs. Downstream of SP-SPR signaling, the following three hormones and neurotransmitters have been found to act on female GSC niche cells to regulate mating-induced increase in female GSCs: (1) neuropeptide F, a peptide hormone produced in enteroendocrine cells; (2) octopamine, a monoaminergic neurotransmitter synthesized in ovary-projecting neurons; and (3) ecdysone, a steroid hormone produced in ovarian follicular cells. These humoral factors are secreted from each organ and are received by ovarian somatic cells and regulate the strength of niche signaling in female GSCs. This review provides an overview of the latest findings on the inter-organ relationship to regulate mating-induced female GSC increase in D. melanogaster as a model. We also discuss the remaining issues that should be addressed in the future.